Rethinking fairness of business and human rights standards in times of challenge for climate protection: a new universal paradigm? - Alina GENTIMIR; Ada-Iuliana POPESCU (Present Environment and Sustainable Development)
Understanding the multivalent dimensions of the climate protection, including its ef¬fects on the rule of law, international and European intergovernmental organizations have de¬cided to act for rethinking the strategy of functioning business and human rights standards in environmental protection general context. The article proposes solutions for such a strategy like coherent macro and micro measures, transversality of action, synergy of normative, independ¬ence of control mechanisms, a closed collaboration established between intergovernmental organizations, Governments and civil society. Would be necessary for human rights holders and State and business enterprises obligations to satisfy exigencies of fairness? Would be taken into consideration the double role of businesses related to activities that impact climate change in the case of all the obligations imposed to business? Would be more efficient for States and, subse¬quently, for all business enterprises to implement “the smart mix of measures”? Using traditional approach of 'black letter' methodology in order to collate, organize and describe legal rules, as well qualitative and quantitative research methods for look to the impact of the law in practice and the role played by public policy and a comparative historical approach for the human rights analysis, the article emphasizes that despite recently lost battles in human rights and climate protection, a general political will currently exists for creation and adoption of a new legal frameworks which incorporates divers and stronger guarantees for a better protection of human rights and environment.